Intuition and missing links in Project Management: a case study from the Elbanna (2015) model - Thomé, Octavio Sanz dos Santos; Nascimento, Alexandre Ferreira; Carvalho Cid de Araujo, Fernando; Farias Filho, José Rodrigues (Brazilian Journal of Operations & Production Management, 2017)
Intuition has become a common theme in project management. Elbanna (2015) examines how environment influences intuition and whether reflexivity mediates the link between intuition and project outcomes. By this way, the aim of this work is to apply Elbanna (2015) methodology in a Brazilian firm in order to contribute for to the model validation and to make a literature review, regarding intuition in project management. Our results contribute to science dialog about intuition and reflexivity in decisory process.